PERAN GUEST SERVICE AGENT DALAM PENANGANAN DAYTRIPPER DIMAYANG SARI BEACH RESORT BINTAN KEPULAUN RIAU - Lora Sasmita; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Mayang Sari Beach Resort is located on Bintan Islan Kepulauan Riau that is the property of nirwana gardens resort. Mayang Sari Beach Resort received various types of tourists who come, especially for vacationand recreation. There is the kind of tourists who come to mayang sari beach resort who called with Daytripper (Traveler,Excurtionist), Guest Service Agent has a important role in daytripper reception.This study aims to determine to know the role of Guest Service Agent in the handling of daytripper at Mayang Sari Beach Resort Bintan Islan Kepulauan Riau. This study using the descriptive qualitative to examine problems that was appointed. The research subjects in this study amounted to 5 people, data collection techniques in this research using observation, the interview and the documentation.The result of this research shows that the role of Guest Service Agent in the handling of Daytripper at Mayang Sari Beach Resort Bintan Islan Kepulauan Riau there are Guest Service Agent who did the role of her based on the Standart Operations Procedure.Keywords : Daytripper,Guest Service Agent,Standart Operations Procedure